2018
DOI: 10.3892/etm.2018.6873
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of levels of D‑dimer and interferon‑γ in pediatric patients with Mycoplasma pneumoniae pneumonia and its clinical implication

Abstract: Levels of D-dimer and interferon-γ (INF-γ) in pediatric patients with Mycoplasma pneumoniae pneumonia (MPP) were assessed to explore its clinical implication in evaluating the disease severity and patients' prognosis. Enrolled in this study as subjects were 185 pediatric patients with MPP who were admitted to the Department of Pediatrics of the Second Affiliated Hospital of Qiqihar Medical University and the First Hospital of Qiqihar City from January 2017 to October 2017 and 115 healthy children who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…Elevated D-D levels may imply that hypercoagulability is prevalent in children with MPP and is more severe in children with RMPP, and that vascular endothelial cell injury caused by an excessive in ammatory response may be involved in the mechanism of lung injury in RMPP. In a previous study, the levels of D-D were found to have decreased signi cantly after a period of treatment, and the nal levels after treatment were higher in a group with severe pneumonia compared with a group having mild pneumonia [20]. Our study found 1 week of treatment was associated with a signi cant decrease in D-D level, although levels remained abnormal in most cases, indicative of a prolonged state of high coagulation and endothelial injury in RMPP.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Elevated D-D levels may imply that hypercoagulability is prevalent in children with MPP and is more severe in children with RMPP, and that vascular endothelial cell injury caused by an excessive in ammatory response may be involved in the mechanism of lung injury in RMPP. In a previous study, the levels of D-D were found to have decreased signi cantly after a period of treatment, and the nal levels after treatment were higher in a group with severe pneumonia compared with a group having mild pneumonia [20]. Our study found 1 week of treatment was associated with a signi cant decrease in D-D level, although levels remained abnormal in most cases, indicative of a prolonged state of high coagulation and endothelial injury in RMPP.…”
Section: Discussionsupporting
confidence: 55%
“…Regarding complications, previous studies have reported that D-D level was positively correlated with extra-pulmonary complications in pediatric patients with MPP [20]; however, extensive research on D-D level and complications has not been reported to date. In a previous study, a higher level of D-D was associated with more extensive and serious thrombosis [8].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Vascular complication is one of the rarest extrapulmonary complications. It has been reported that children with MPP had a high risk of blood coagulation and thrombosis [11,13,14] . However, there have been only a few reported cases of MPP-associated thrombosis, and data on risk factors, clinical characteristics, treatment and long-term prognosis of the larger studies especially the risk factors are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated D-D levels may imply that hypercoagulability is prevalent in children with MPP and is more severe in children with RMPP and that vascular endothelial cell injury caused by an excessive in ammatory response may be involved in the mechanism of lung injury in RMPP. In a previous study, the levels of D-D were found to have decreased signi cantly after a period of treatment, and the nal levels after treatment were higher in a group with severe pneumonia than in a group with mild pneumonia [21]. Our study found that one week of treatment was associated with a signi cant decrease in D-D levels, although levels remained abnormal in most cases, indicative of a prolonged state of high coagulation and endothelial injury in RMPP.…”
Section: Discussionmentioning
confidence: 82%